2014
DOI: 10.1037/a0037794
|View full text |Cite
|
Sign up to set email alerts
|

The role of first use of inhalants within sequencing pattern of first use of drugs among Brazilian university students.

Abstract: The present study investigated the role of first use of inhalants within a first drug sequencing pattern. In a representative sample of university students from 27 Brazilian capitals (n=12,711), we analyzed the patterns of transition from/to first use of inhalants to/from the first use of alcohol, tobacco, cannabis, cocaine, hallucinogens, ecstasy, amphetamines, prescription opioids, and tranquilizers. Cox proportional hazards models were used to analyze data. Drugs that were not specified as the pair of drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In Brazil, our group recently conducted some studies using the same sample of the present study . We found that cannabis use does not seem to precede the use of inhalants and amphetamines , despite having prevalence of cannabis use (19.8%) higher than these other drugs (16.6% and 8.4%, respectively).…”
Section: Discussionsupporting
confidence: 51%
“…In Brazil, our group recently conducted some studies using the same sample of the present study . We found that cannabis use does not seem to precede the use of inhalants and amphetamines , despite having prevalence of cannabis use (19.8%) higher than these other drugs (16.6% and 8.4%, respectively).…”
Section: Discussionsupporting
confidence: 51%
“…However, subjects who initiated inhalants and who did not start the sequence with tobacco were more at risk to initiate OID first or after tobacco or cannabis. Inhalant use is rare in France [42] but some research conducted in Brazil, where these substances are used widely, showed that first use of inhalants followed tobacco initiation but preceded the first use of some illicit substances, suggesting that inhalants should be included in the second step of the gateway model in association with cannabis [43,44] .…”
Section: Gateway Processmentioning
confidence: 99%
“…One of the signaling behaviors that researchers and policy makers are interested in for intervention is early cigarette smoking (Castaldelli-Maia, Nicastri, Garcia de Oliveira, Guerra de Andrade, & Martins, 2014; Mathers, Toumbourou, Catalano, Williams, & Patton, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In the review by Mathers et al (2006)—based on longitudinal studies from 1980 to 2005 that looked at the association between tobacco use under 18 years of age and outcomes at 18 years of age or older—early tobacco smoking was a risk marker for later alcohol initiation and alcohol-related problems, such as alcohol abuse, dependence, and binge drinking (Brook et al, 2002; Ellickson et al, 2001; Lewinsohn, Rohde, & Brown, 1999). A retrospective study that used a non-U.S. sample evaluated the transitions of drug use involving inhalants, and also found a transition from tobacco to inhalants (Castaldelli-Maia et al, 2014). In longitudinal studies that examined the association between adolescent smoking and substance abuse, age at follow-up ranged from 18 to 32 years; the majority of follow-up times were under age 30 (Mathers et al, 2006).…”
Section: Introductionmentioning
confidence: 99%